IMR 665: Management of Audio Visual Records & Archives. Individual assignment: Article summary / Azianni Husain - Husain, Azianni (2015)
Article on: Article 1 - “Preservation in the age of google digitization, digital preservation and dilemmas” Article 2 - “The conversation and preservation of film and magnetic materials (1): film materials"